Isolation and characterization of bacteriophages from the human skin microbiome that infect Staphylococcus epidermidis. (30th March 2021) - Valente, Luca G; Pitton, Melissa; Fürholz, Monika; Oberhaensli, Simone; Bruggmann, Rémy; Leib, Stephen L; Jakob, Stephan M; Resch, Grégory; Que, Yok-Ai; Cameron, David R
ABSTRACT: Phage therapy might be a useful approach for the treatment of nosocomial infections; however, only few lytic phages suitable for this application are available for the opportunistic pathogen, Staphylococcus epidermidis . In the current study, we developed an efficient method to isolate bacteriophages present within the human skin microbiome, by using niche-specific S. epidermidis as the host for phage propagation. Staphylococcus epidermidis was identified on the forehead of 92% of human subjects tested. These isolates were then used to propagate phages present in the same skin sample. Plaques were observable on bacterial lawns in 46% of the cases where S. epidermidis was isolated. A total of eight phage genomes were genetically characterized, including the previously described phage 456. A total of six phage sequences were unique, and spanned each of the major staphylococcal phage families; Siphoviridae ( n = 3), Podoviridae ( n = 1) and Myoviridae ( n = 2). One of the myoviruses (vB_SepM_BE06) was identified on the skin of three different humans. Comparative analysis identified novel genes including a putative N-acetylmuramoyl-L-alanine amidase gene. The host-range of each unique phage was characterized using a panel of diverse staphylococcal strains ( n = 78). None of the newly isolated phages infected more than 52% of the S. epidermidis strains tested ( n = 44), and non- S. epidermidis strains where rarely infected, highlighting the narrow host-range of the phages. One of the phages (vB_SepM_BE04) was capable of killing staphylococcal cells within biofilms formed on polyurethane catheters. Uncovering a richer diversity of available phages will likely improve our understanding of S. epidermidis -phage interactions, which will be important for future therapy. Abstract : Human skin is a useful source of bacterial viruses (phages) that have the capacity to lyse pathogenic bacteria and to destroy biofilms.